2021
DOI: 10.2166/wst.2021.313
|View full text |Cite
|
Sign up to set email alerts
|

Porous g-C3N4 with defects for the efficient dye photodegradation under visible light

Abstract: Porous graphitic carbon nitride (p-C3N4) was fabricated via simply pyrolyzing treatment of graphitic carbon nitride (g-C3N4). The defects could be introduced into the structure of g-C3N4 by the broken of some bonds, which was beneficial for the generation of electron-hole pairs and restraining their recombination. Compared with g-C3N4, p-C3N4 showed a narrow band gap to promote the utilization of visible light. Furthermore, the porous structure also increased the specific surface area to maximize the exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The optical properties of the produced materials were investigated by UV-VIS absorption and PL spectroscopies ( Figure 9 ). As observed in Figure 9 a, pure g-C 3 N 4 shows an absorption maximum at around 384 nm (3.23 eV), arising from the n → π* transitions caused by the electron transfer from a nitrogen non-bonding orbital to an aromatic anti-bonding orbital [ 100 , 101 ], and an absorption onset at ca. 450 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties of the produced materials were investigated by UV-VIS absorption and PL spectroscopies ( Figure 9 ). As observed in Figure 9 a, pure g-C 3 N 4 shows an absorption maximum at around 384 nm (3.23 eV), arising from the n → π* transitions caused by the electron transfer from a nitrogen non-bonding orbital to an aromatic anti-bonding orbital [ 100 , 101 ], and an absorption onset at ca. 450 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is to be noted that a porous g-C 3 N 4 catalyst prepared by a facile two-step method in a previous study showed good stability over three cycles of photodegradation of the dyes MO and Rh B. 51 Also, a g-C 3 N 4 composite with TiO 2 was used as a photocatalyst to degrade Rh B and MB, with the reported efficiency ranging from 96% to 88% and 95% to 85%, respectively, after 4 runs of recycling the photocatalyst. 52 Also, when g-C 3 N 4 was used with CeVO 4 as a composite photocatalyst in recycling experiments, MB dye was degraded by 98.2% in the first cycle and then the efficiency was reduced to 92.37% in the fourth cycle; this reduced efficiency was attributed to the physical loss of the catalyst and some adsorbed dye molecules on the catalyst.…”
Section: Photocatalytic Activity Studiesmentioning
confidence: 91%
“…The photocatalytic process occurs with the assistance of active radicals produced by these photochemical reactions. Radicals, such as ˙O 2 − , e − , h + , and ˙OH are usually responsible for the dye degradation; 51,52 however, not all radicals contribute equally to the degradation. Therefore, the dominant contribution from the particular species can be found via scavenger tests, which is simply the regular photocatalysis experiment but with the addition of scavenger molecules to the reactant solution.…”
Section: Photocatalytic Activity Studiesmentioning
confidence: 99%
“…The p-C 3 N 4 exhibited a narrow band gap for promoting visible light utilization as compared with g-C 3 N 4 . p-C 3 N 4 degraded 90% of the MO dye in 90 min, which was sufficiently higher than the activity of g-C 3 N 4 (only 19% after 90 min) under visible light [ 129 ]. Similarly, the results discussed in the doping section about the P and S-co-doped g-C 3 N 4 indicate that P and S co-doping causes defects in the sample structure.…”
Section: Crystal Phase Control and Defects Introductionmentioning
confidence: 99%